Simulation numérique de la propagation de fissure dans les superalliages monocristallins: Simulation numérique de la propagation de fissure dans les monocristaux - Bouvard, Jean-Luc; Chaboche, Jean-Louis; Feyel, Frédéric; Gallerneau, Franck (European Journal of Computational Mechanics, 2007)
In this study, a numerical method is developped to simulate fatigue crack growth. This method is based on a numerical coupled analysis using a cohesive zone modelling under cyclic loading in order to develop a coupled predictive approach of the crack growth. First, we present this damage law, then its validation by a convergence study of the solution with mesh size. We apply this model to the crack growth calculations in the case of a smooth specimen with a precracking made with a single crystal superalloy. Finally, we define the method to calibrate the cohesive zone model parameters on the base of experimental tests performed in pur fatigue regime.